Weight management program focusing on body composition and physical activity among healthcare staff at a primary care clinic - Kamaruzaman, Nor Azam; Abd Rahman, Mohd Aizuddin; Pasi, Hafizah (Academy of Family Physicians of Malaysia (AFPM), 2023)
Overweight and obesity are increasingly prevalent with a ratio of 1 in 2 among adult Malaysian. 65 percent of staff in a primary care clinic was found to be either obese or overweight. A program with the aim to empower clinic members to achieve reduction in weight and body fat percentage (BF%), improve fitness and build teamwork was initiated in August 2022. In a period of 4 months, the highest percentage reduction for BMI is 10 while BF% is 15. In conclusion, self-sustaining group exercise program and monitoring using body composition analysis showed positive outcome.